2021
DOI: 10.1177/10664807211005066
|View full text |Cite
|
Sign up to set email alerts
|

Counseling Clients Who Have Experienced Undisclosed Infidelity

Abstract: Undisclosed infidelity is when one partner suspects betrayal, but the other partner denies it. While the literature is replete with helping couples heal from disclosed infidelity, very few scholarly articles address working with betrayed partners of undisclosed infidelity. Researchers indicated the accuracy of detecting undisclosed infidelity and the propensity for betrayers to lie when confronted, thus counselors need to be aware of the traumatic effects associated with undisclosed infidelity to skillfully su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…In fact, the Spring Pew Global Attitudes Survey (2013) showed that the majority of the respondents in each country that they surveyed, including the Philippines, deemed that infidelity or having an affair is morally unacceptable. Infidelity can have devastating effects in a relationship (Moore, 2021), and research suggests that being betrayed/cheated on by a partner can be very stressful (Roos et al, 2019), as well as traumatizing (Curtis et al, 2021;Scuka, 2015;Vossler & Moller, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the Spring Pew Global Attitudes Survey (2013) showed that the majority of the respondents in each country that they surveyed, including the Philippines, deemed that infidelity or having an affair is morally unacceptable. Infidelity can have devastating effects in a relationship (Moore, 2021), and research suggests that being betrayed/cheated on by a partner can be very stressful (Roos et al, 2019), as well as traumatizing (Curtis et al, 2021;Scuka, 2015;Vossler & Moller, 2014).…”
Section: Introductionmentioning
confidence: 99%